PERAN NILAI PELANGGAN PERSEPSIAN PADA PENERAPAN THEORY OF PLANNED BEHAVIOUR DALAM PEMBELIAN PRODUK ORGANIK - Oktavia Pratama Putri; Waluyo Budi Atmoko; Finisha Mahaestri Noor (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
his study aims to examine the effect of the intention to buy organic products on the buying behavior of organic products. Intention to buy a strong organic product will encourage someone to buy behavior. Data obtained through questionnaires distributed to potential users of organic products. The sampling technique used is a two-stage cluster sampling technique with a population of students residing in Surakarta colleges of 200 respondents. Hypothesis testing is done by using SEM and regression analysis. The study found results: (1) purchase intention has a significant effect on buying behavior, (2) the implementation plan does not mediate the relationship between purchase intention and buying behavior, (3) perceived behavioral control has a significant effect on purchase intention, (4) subjective norms have a significant effe ct on purchase intention, (5)attitude has no effect on purchase intention, (6) perceived customer value has a significant effect on attitude.